Seismic site classification of Nakhon Nayok City, central Thailand, using the MASW technique - Thitimakorn, Thanop; Arjwech, Rungroj; Kupongsak, Sasikan (Frontiers in Earth Science, 2023)
Shear-wave velocity (Vs) of soils in Nakhon Nayok City, Central Thailand were determined using the Multi-Channel Analysis of Surface Wave technique. The Vs. of 35 tested sites were weighted average to 30 m depth based on the National Earthquake Hazards Reduction Program (NEHRP) criteria, which revealed NEHRP site classes C, D, and E within the study area. Soil class C was found in the north of the city. Moreover, most of the residential area of Nakhon Nayok City is positioned on soil classes D and E. The soil in the area of study has an amplification value ranging from 1.4 to 3.9. The central and southwestern parts of the city, which mainly consist of soft sediments, have a higher amplification value than that in the northern part, which mainly consists of coarse grain soils of colluvial deposits. Based on the NEHRP and amplification value, the Nakhon Nayok City area will experience some effect from ground shaking from nearby and far away earthquake seismic sources.